Removal of phosphates from aqueous solutions by using bauxite: II.activation study - Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2003)
In this study, acid treatment and heat treatment methods have been investigated in order to enhance the phosphate adsorption capacity of bauxite. For this purpose, a series of bauxites treated with 0.1–1.0 M HCl and another one heated at various temperatures between 200 and 1000 °C were subjected to standardized orthophosphate adsorption tests. Besides determining chemical and mineralogical compositions, TGA and DTA were performed and point of zero net proton charge (PZNPC), surface area, mean particle size and porosity were measured for selected samples. The results have shown that the acid treatment of bauxite has a negative effect on the phosphate adsorption capability. On the other hand, it has been observed that the phosphate adsorption capacity of bauxite could be increased by heating. The optimum heating temperature was determined as 600 °C. Bauxite heated at 600 °C exhibited about an eight-fold increase in surface area compared with raw bauxite. The results showed that the activation of bauxite occurred via dehydration of boehmite and diaspore, being the hydrated mineral phases. Maximum adsorption efficiencies for ortho-, tripoly- and glycerophosphates were achieved in the slightly acidic pH range. It was found that the adsorption capacities of thermally-activated bauxite for all phosphate species investigated were higher than that of raw bauxite. But the increase in adsorption efficiency is not proportional to the increase in specific surface area. It was found that the relative adsorptivity of phosphate species investigated is in the order of orthophosphate > tripoly(phosphate) > glycerophosphate. In addition, it was found that the desorption trends of these phosphate species were similar to the results obtained for raw bauxite.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Phosphate adsorption; Bauxite; Heat activation; Acid activation; Activation mechanism